Anomalous behaviour of ozone under COVID-19 and explicit diagnosis of O3-NOx-VOCs mechanism. Issue 2 (February 2021) - Rathod, A.; Sahu, S.K.; Singh, S.; Beig, G.
Abstract: Air pollution is linked to higher rates of human mortality especially those infected with COVID 19. Ozone is a harmful pollutant and is responsible for many health issues. However, some reports suggest that ozone is a strong disinfectant, and can kill the viruses. We hereby, report on the vulnerability of ozone due to COVID-19 lockdown whose levels flutter from surging to saturation in a highly polluted Indian capital, due to significant decline in anthropogenic emissions of ozone precursors. Average observed levels stabilized at 30 ppb, 12 ppb, 740 ppb, and 900 ppb for ozone (O3 ), nitrogen dioxide (NO2 ), carbon monoxide (CO) and volatile organic compounds (VOCs) respectively during lockdown period from 27 th March to 10 th April 2020. The NO2, CO and VOC declined by 50 %, 37 %, 38 % respectively during the lockdown period of 2020 as compared to similar period in 2019. The anomalous response of ozone during the lockdown is explained by resolving the poorly known complex O3 -NOx -VOCs mechanism with the help of data from air monitoring stations in Delhi, India. The data obtained from this study advances the fundamental understanding of ozone chemistry that may lead to improved ozone parameterization in chemical transport models and better planning of ozone risk management strategies for any global mega cities. Abstract : Ozone, O3, COVID-19, Anthropogenic, NOx, Pollutant.